(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Urinary stone disease (urolithiasis) is a chronic, relapsing metabolic disease characterized by the presence of stones (concrements) in the urinary system, that is, in the kidney, bladder and urinary tract. Sometimes the terms urolithiasis and nephrolithiasis are used as synonyms, but nephrolithiasis can be called only the presence of stones in the kidney (not in other parts of the urinary system).